2005
DOI: 10.1111/j.1774-9987.2005.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Calcification in Patients With End‐stage Renal Disease

Abstract: Vascular calcifications are very frequent extraosseous calcifications in patients with chronic renal disease. They occur in the intima and in the media. They are associated with decreased arterial elasticity and increased mortality. The risk factors are: advanced age, duration of dialysis treatment, diabetes, increased phosphate concentration, the dose of Ca-containing phosphate binders and inflammation. It is now well established that vascular smooth muscle cells actively take up phosphate to form bioapatite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…It is produced by the liver and secreted into the bloodstream and plays an anti-inflammatory role by inhibiting lipopolysaccharide-induced tumor necrosis factor-α. Furthermore, recent studies suggested that fetuin-A could act as a protective factor to inhibit ectopic calcification in uremic patients and that the decreased serum fetuin-A concentration was associated with a higher mortality in dialysis patients [18,19,20,21,22]. However, the role of fetuin-A in patients with AKI is not well studied.…”
Section: Discussionmentioning
confidence: 98%
“…It is produced by the liver and secreted into the bloodstream and plays an anti-inflammatory role by inhibiting lipopolysaccharide-induced tumor necrosis factor-α. Furthermore, recent studies suggested that fetuin-A could act as a protective factor to inhibit ectopic calcification in uremic patients and that the decreased serum fetuin-A concentration was associated with a higher mortality in dialysis patients [18,19,20,21,22]. However, the role of fetuin-A in patients with AKI is not well studied.…”
Section: Discussionmentioning
confidence: 98%
“…Calcification in atherosclerotic lesions is relatively common and is implicated as a risk factor for increased cardiovascular morbidity and mortality [24, 25]. Vascular calcification is enhanced with advanced age, chronic renal failure, diabetes and inflammation [26]. We have previously demonstrated that carotid atherosclerotic plaque calcification is a structural surrogate marker for carotid plaque stability [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hi per tan si yon, dia be tes mel li tus, hi per li pi de mi ve si ga ra içi mi bu tip kal si fi kas yon lar için risk fak tör le ri dir. 6 Me di al kalsi fi kas yon lar ise di a be tik ler de, ile ri yaş lar da ve kronik böb rek yet mez li ği var lı ğın da sık lık la iz le nir. Me di al kal si fi kas yon lu has ta la rın ya şa ma oran la rı -nın in ti mal kal si fi kas yon lu has ta la ra gö re da ha iyi ol du ğu göz len miş tir.…”
Section: Kro Ni̇k Böb Rek Yet Mez Li̇ ğİ Ve Vas Kü Ler Kal Si̇ Fi̇ Kas Yonunclassified